Dupilumab treatment reduces caregiver-reported skin pain in patients with moderate-to-severe atopic dermatitis aged 6 months to 5 years - Paller, Amy S.; Silverberg, Jonathan I.; Gonzalez, Mercedes E.; Schneider, Lynda C.; Sidbury, Robert; Chen, Zhen; Bansal, Ashish; Wang, Zhixiao; Prescilla, Randy (Frontiers in Pediatrics, 2024)
Background: Moderate-to-severe atopic dermatitis (AD) often has a profound impact on the quality of life of young children and their caregivers. One of the most burdensome symptoms reported by patients is skin pain. Methods: This post hoc analysis focuses on the impact of dupilumab treatment on skin pain in young children using data from the LIBERTY AD PRESCHOOL part B (NCT03346434), a 16-week randomized, double-blind, placebo-controlled, phase 3 study in 162 children aged 6 months to 5 years with moderate-to-severe AD receiving dupilumab or placebo, plus topical corticosteroids (TCS). Analyses were performed on the full analysis set and subgroups of patients who did not achieve an Investigator’s Global Assessment score of 0 or 1 (IGA >1 subgroup), or who did not achieve a 75% improvement from baseline in the Eczema Area and Severity Index (< EASI-75 subgroup), at week 16 (patients who did not achieve the primary or key secondary endpoints in LIBERTY AD PRESCHOOL part B). Results: At week 16, change from baseline in the skin pain NRS was significantly greater in the dupilumab group vs the placebo group (−3.93 vs −0.62, p<0.0001) and significantly more patients receiving dupilumab vs placebo achieved a clinically meaningful improvement at week 16 (47.2% vs 10.8%, P < .0001). Similar results between dupilumab vs placebo were seen in the two subgroups IGA >1 and